Biosorption of Metals Ion on Methanol Dehydrogenase Activity Test of Bradyrhizobium japonicum USDA110 - Kurniawati, Novita; Pertiwiningrum, Ambar; Fitriyanto, Nanung Agus; Erwanto, Yuny; Abidin, Mohammad Zainal (2018)
This research aims to know effect of absorption metals ion (bisorption) which have different group elements on methanol dehydrogenase (MDH) activity test of nitrogen fixation bacteria Bradyhizobium japonicum USDA 110. Ten of metals ion 30µM concentration were tested to grow Bradyhizobium japonicum USDA 110 in diluted one per ten of nutrient medium. The results of MDH activity test shown bacterial grown without added metal ion has similar MDH activity with bacterial added calsium ion/Ca2+ . Highest enzymatic activity shown on bacterial grown with added magnesium/Mg2+ was 0.08 (U/mg). MDH require to grown on anerobic condition specially simbiotic Bradyhizobium japonicum USDA 110 bacteria. Addition metal ion of magnesium/Mg2+ accelerate bacterial growth 2.6 times and MDH activity 1.28 times than without added metal ion. This research has deduce during anerobic condition on soil and symbiotic proces, metal ions specially calsium and magnesium require to add on plant growth medium to accelerate growth Bradyhizobium japonicum bacteria which well known as bacterial symbiotic on soy bean roots.